Publishing data to support the fight against human vector-borne diseases. (3rd November 2022) - Edmunds, Scott C; Fouque, Florence; Copas, Kyle A; Hirsch, Tim; Shimabukuro, Paloma Helena Fernandes; Andrade-filho, José Dilermando; Marceló, Catalina; Morales, Carlos Andrés; Lesmes, María Camila; Fuya, Patricia; Méndez, Sergio; Cadena, Horacio; et al.
Abstract: Vector-borne diseases are responsible for more than 17% of human cases of infectious diseases. In most situations, effective control of debilitating and deadly vector-bone diseases (VBDs), such as malaria, dengue, chikungunya, yellow fever, Zika and Chagas requires up-to-date, robust and comprehensive information on the presence, diversity, ecology, bionomics and geographic spread of the organisms that carry and transmit the infectious agents. Huge gaps exist in the information related to these vectors, creating an essential need for campaigns to mobilise and share data. The publication of data papers is an effective tool for overcoming this challenge. These peer-reviewed articles provide scholarly credit for researchers whose vital work of assembling and publishing well-described, properly-formatted datasets often fails to receive appropriate recognition. To address this, GigaScience 's sister journal GigaByte partnered with the Global Biodiversity Information Facility (GBIF) to publish a series of data papers, with support from the Special Programme for Research and Training in Tropical Diseases (TDR), hosted by the World Health Organisation (WHO). Here we outline the initial results of this targeted approach to sharing data and describe its importance for controlling VBDs and improving public health.